Analysis of Portugal's refuse derived fuel strategy, with particular focus on the northern region. (20th December 2020) - Berardi, Patricia; Almeida, Manuel Fonseca; Lopes, Maria de Lurdes; Maia Dias, Joana
Abstract: Portugal's performance concerning the Refuse Derived Fuel (RDF) strategy, with particular focus on perspectives for the Northern Region based on the current status of integrated municipal waste management systems in that region, was evaluated. Legal documents, official reports and the market were analyzed. The 2015 national installed capacity of waste treatment technologies, from which the high calorific value fraction (HCVF) for RDF production is obtained, is not far from what was predicted for 2013. However, only around 11% of the HCVF had such destiny and the amount of effectively produced RDF was only 30% of the material sent to RDF production (around 30 kt). In Northern Portugal, no RDF production plant was in operation in 2015; the amount of HCVF was estimated to range from 105 to 204 kt for 2015 and around 2.4 times more is expected in 2020. The strategy laydown for RDF failed so far, and thus, low diversion of waste from landfills is observed, mostly due to low landfill taxes and low HCVF quality, resulting in RDF being non-competitive with the imported higher quality product from countries with very high landfilling fees. Moreover, co-incineration and dedicated recovery solutions are scarce. In the Northern region, the HCVF may be treated in the existing municipal waste incinerator or the RDF might be recovered in new dedicated plants, receiving also non-hazardous waste fractions from other origin. Overall, to ensure a sustainable municipal waste management, the intensification of the reuse, preparation for reuse and recycling of waste components from source segregated collection must be significantly promoted.